Using lightweight airframe materials in aircraft structures and investigating potential reinforcement effects with sustainable aviation fuels: An analysis of environmental and economic impacts - Anna J. G. Hellmann; Alexander Barke; Wolfgang Heinze; Sebastian Heimbs; Thomas S. Spengler (Journal of Industrial Ecology, 2025)
Using lightweight materials in aircraft structures, especially carbon fiber reinforced polymer (CFRP), can be an option for achieving aviation's ambitious emission reduction goals. However, using CFRP can be associated with adverse environmental and economic impacts, which can relativize its potential benefits. Nevertheless, the extent of the potential advantages and disadvantages of the increased use of CFRP in the entire airframe is still uncertain, as existing studies relate to specific airframe components or estimated weight savings. This article aims to close this gap by developing detailed life cycle inventories (LCIs) for aircraft with CFRP structures and analyzing the environmental and economic impacts during aircraft production and use. Furthermore, potential reinforcement effects from using sustainable aviation fuels (SAFs) in such aircraft are investigated to determine the overall environmental and economic impacts. For this purpose, three aircraft configurations with different CFRP content are modeled using the aircraft design program “Preliminary Aircraft Design and Optimization”. Afterward, detailed LCIs are developed, and life cycle assessment and environmental life cycle costing are applied. Subsequently, an analysis is conducted where SAFs replace fossil kerosene to investigate the potential for further reductions of environmental and economic impacts. The results of the analysis indicate that increasing the CFRP content in the airframe reduces environmental impacts during production and use. Despite higher production costs, more cost‐effective flight operations are possible. Additionally, there is a reinforcement effect through using SAFs in aircraft with increased CFRP content, which can further reduce climate‐damaging emissions by several magnitudes more compared to lightweight materials alone.

Virus infections of the European Eel in North Rhine Westphalian rivers - Linna Danne; Lisa Horn; Anita Feldhaus; Daniel Fey; Sebastian Emde; Heike Schütze; Mikolaj Adamek; John Hellmann (Journal of Fish Diseases, 2022)
Viral infections have been suggested to play a role in the decline of the panmictic population of the European eel ( Anguilla anguilla ). However, despite the importance of knowledge about pathogenic eel viruses, little is known about their spread in the wild European eel population and only a few eel pathogenic viruses have been described so far. In this study, we aimed to investigate the health status of the A. anguilla stock in North Rhine Westphalia (NRW) State of Germany. For this purpose, we examined tissue samples of 16 elvers, 100 yellow eels and 6 silver eels, sampled from the rivers Rhine, Lippe and Ems. Virus detection was performed via a combination of cell culture and PCR. Next to the detection of frequently encountered pathogenic eel viruses (anguillid herpesvirus 1 and eel virus European X (EVEX)), we isolated the eel picornavirus 1 (EPV‐1) from tissue of yellow eels and elvers and demonstrate the distribution of EPV‐1 in wild eel population in NRW.

Assessing the Influence of Water Constituents on the Radiative Heating of Laptev Sea Shelf Waters - Mariana A. Soppa; Vasileios Pefanis; Sebastian Hellmann; Svetlana N. Losa; Jens Hölemann; Fedor Martynov; Birgit Heim; Markus A. Janout; Tilman Dinter; Vladimir Rozanov; Astrid Bracher (Frontiers in Marine Science, 2019)

Nutzung neuronaler Netzwerke zur Erstellung von Bodenrichtwertkarten - Ulrich F. Voos; Sebastian Hellmann; Frank Dickmann (KN - Journal of Cartography and Geographic Information, 2013)